Alison Settle, Editor of British Vogue (1926–1935): Habitus and the Acquisition of Cultural, Social, and Symbolic Capital in the Private Diaries of Alison Settle. (2nd January 2019) - Coser, Ilaria
Abstract: Alison Settle was celebrated in her lifetime as the Grande Dame of British fashion journalism. Her career extended over five decades, from the mid-1910s until the mid-1970s, including nearly a decade as editor of British Vogue in the interwar period (1926–1935). This article examines the strategies she adopted to acquire and accumulate the specific knowledge, reputation and connections required to perform her professional role as a "cultural businesswoman" of the world of fashion. This research is based on private diaries that Settle wrote in the early 1930s, during the second half of her editorship at Vogue . The analysis of Settle's journals focuses on the daily routines she performed in the public sphere, assiduously recorded in the form of lists of social engagements. Settle did not write specifically about dress and fashion in her journals. Yet her life was organised around, shaped by, and intertwined with her profession, making her diaries an invaluable primary source to investigate the social activities and the lifestyle that made Settle the editor of Vogue . This research applies an interdisciplinary methodology to develop an understanding of their content through the critical framework of Bourdieu's theories—specifically through the concepts of habitus, cultural capital, and field .